2023
DOI: 10.1101/2023.03.01.23286637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the Performance of Expired and Unexpired BinaxNOW COVID Rapid Antigen Test Kits Using Positive and Negative Controls

Abstract: Rapid antigen tests are widely used to diagnose infection with SARS-CoV-2, and millions of kits have been distributed for free by government agencies. However, unused and expired kits beyond their final expiration dates remain prevalent in people's homes. This study aimed to determine the accuracy of expired BinaxNOW COVID rapid antigen test kits. 100 expired and 100 unexpired test kits were checked for sensitivity and specificity using positive and negative controls, respectively. The results showed that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…15 There is limited peer-reviewed information available about the accuracy of expired kits. It has been shown that they work well when robust antigen laden "positive controls" are used to assess their accuracy, 16 but more thorough analysis data is not available. In response to this knowledge gap, our study aims to evaluate the performance of expired kits at the lower bound of their detection capability, to inform future public health decision-making.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…15 There is limited peer-reviewed information available about the accuracy of expired kits. It has been shown that they work well when robust antigen laden "positive controls" are used to assess their accuracy, 16 but more thorough analysis data is not available. In response to this knowledge gap, our study aims to evaluate the performance of expired kits at the lower bound of their detection capability, to inform future public health decision-making.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…There is limited peer-reviewed information available about the accuracy of expired kits. It has been shown that they work well when robust antigen-laden “positive controls” are used to assess their accuracy ( 16 ), but more thorough analysis data are not available. In response to this knowledge gap, our study aims to evaluate the performance of expired kits at the lower bound of their detection capability to inform future public health decision-making.…”
Section: Introductionmentioning
confidence: 99%